Evaluating the Effectiveness and Ethical Considerations of CCTV Surveillance in Public Spaces: A Cybersecurity Perspective - Yulius Sutanto (International Journal of Information System and Innovative Technology, 2024)
CCTV surveillance plays a crucial role in modern security systems, widely implemented in public spaces, transportation hubs, and commercial settings to enhance safety and deter crime. Technological advancements, including artificial intelligence, facial recognition, and real-time analytics, have expanded its capabilities, positioning CCTV as both a preventive and investigative tool. However, debates persist regarding its actual impact on crime reduction, with some studies indicating that CCTV lowers criminal activity in well-monitored locations, while others argue that it merely displaces crime to unmonitored areas. Additionally, concerns over cybersecurity risks, data privacy, and unauthorized access to surveillance networks present significant challenges that threaten public trust and system reliability. The global expansion of CCTV further raises ethical and legal dilemmas related to mass surveillance, government overreach, and individual privacy rights. This study critically examines the effectiveness of CCTV in crime prevention, its role in security preparedness, and the cybersecurity vulnerabilities associated with its implementation. By reviewing key research findings, it offers policy recommendations to strengthen CCTV deployment through enhanced cybersecuritymeasures, privacy protections, and ethical oversight. These insights aim to assist policymakers, law enforcement agencies, and cybersecurity professionals in optimizing CCTV applications while mitigating the risks of surveillance misuse.